2013
DOI: 10.1089/biores.2013.0026
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Recombinant Antibody Specific for i Blood Group Antigen, a Mesenchymal Stem Cell Marker

Abstract: Multipotent mesenchymal stem/stromal cells (MSCs) offer great promise for future regenerative and anti-inflammatory therapies. Panels of functional and phenotypical markers are currently used in characterization of different therapeutic stem cell populations from various sources. The i antigen (linear poly-N-acetyllactosamine) from the Ii blood group system has been suggested as a marker for MSCs derived from umbilical cord blood (UCB). However, there are currently no commercially available antibodies recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Inhibitory factors secreted by SS-MNCs to prevent further EPC network formation is consistent with the physiological function of pericytes to stabilize nascent microvessel structures. 1,2 The Matrigel™ matrix is also limited in its ability to offer thorough analysis of SS-MNC pericyte function due to the lack of EC network stability we observed after 24 h. The immature SS-MNCs may require additional time to differentiate towards a pro-angiogenic mural cell type, which we observed by 2 weeks of coculture with EPCs based on the support of EPC network formation (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Inhibitory factors secreted by SS-MNCs to prevent further EPC network formation is consistent with the physiological function of pericytes to stabilize nascent microvessel structures. 1,2 The Matrigel™ matrix is also limited in its ability to offer thorough analysis of SS-MNC pericyte function due to the lack of EC network stability we observed after 24 h. The immature SS-MNCs may require additional time to differentiate towards a pro-angiogenic mural cell type, which we observed by 2 weeks of coculture with EPCs based on the support of EPC network formation (Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, groups have reported methods to improve the purity of MSCs by using surface antigens. 4,20 While this approach can yield pure populations of MSCs, the time and cell doubling rate required to reach therapeutically-relevant cell numbers can lead to senescent cells that no longer possess angiogenic characteristics of MSCs observed at earlier passages. 13,24,44 In this work, we found a highly proliferative population of MNCs from cord blood morphologically resembling pericytes was possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the reported expression of i antigen on human mesenchymal stem cells (55), it was opportune to investigate the effect of sulfation on its expression. Earlier studies from our group (36) showed that i antigen expression on the unbranched T2-T2 sequence is masked on KS chains that are fully 6-sulfated on Gal and GlcNAc residues.…”
Section: Discussionmentioning
confidence: 99%
“…Here we use an array of sequence-defined glycans to make for the first time a close comparison of the glycan-binding specificities of the five antibodies that recognize human stem cells: mAbs TRA-1–60, TRA-1–81 and FC10.2 that broadly recognize ES, iPS and EC cells, an anti-i P1A ELL directed at linear poly- N -acetyllactosamine sequences (29), which according to ref (30) is predicted to recognize mesenchymal stem cells, and R-10G that recognizes ES and iPS cells. To assign the determinant of mAb R-10G, which is clearly different from those of the four other antibodies, we use the Beam Search microarray approach (28) using an antigen-positive KS polysaccharide as the macromolecular start-point.…”
mentioning
confidence: 99%